A Solid-Phase Enzymeimmunoassay for Human Albumin - HIRATA, MEISEI; ISOBE, JUNICHI; MIZUNO, YOUKO; ENDOU, YUKIKO; SHOUNO, KAZUKO; SHIMA, KENJI; GOTOU, MASARU (Japanese Journal of Clinical Chemistry, 1986)
An enzymeimmunoassay (EIA) was established for measuring human urinary albumin. The assay was based on a two-step sandwitch method by using polystyrene beads as the solid-phase. Measurement covered from 5 to 1,000 ng/ml, and its coefficients of veriation of intraassay and interassay were 5.0-9.0% and 8.0-12.4% respectively. Dilution test showed a good linearity in the range of 0.1-1.0 O.D., and the recovery ratio was between 96-124%, This EIA showed a good correlation with an commercially available RIA system (r=0.974, n=78). The urinary albumin of normal and diabetic subjects, free of proteinuria by testtape method, was 7.12±3.96 and 31.87±52.72 mg/g·cr respectively, and the latter group showed a significantly (p<0.025) higher urinary albumin. This EIA could be a useful system for detecting trace amount of urinary albumin and be applied to the diagnosis of early renal dysfunction.